2019
DOI: 10.1093/jxb/erz470
|View full text |Cite
|
Sign up to set email alerts
|

Single-base resolution methylomes of cotton CMS system reveal epigenomic changes in response to high-temperature stress during anther development

Abstract: Here, cytosine methylation at single-base resolution across the whole genome of cotton (Gossypium hirsutum L.) anthers was mapped using the whole-genome bisulfite sequencing technique, and the methylome changes associated with high-temperature (HT) stress were analysed in two cotton lines of the CMS system with contrasting HT stress tolerance. The cotton anther genome was found to display approximately 31.6%, 68.7%, 61.8%, and 21.8% methylation across all sequenced C sites and in the CG, CHG and CHH sequence c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 86 publications
7
36
0
1
Order By: Relevance
“…It has been reported that N6‐methyldeoxyadenine (6 mA) is a transgenerational epigenetic signal for mitochondrial stress adaptation in Caenorhabditis elegans , and Zhang et al . reported that more transposable elements were demethylated under high‐temperature stress in cotton . Combining our findings that the high‐resistance mutants against SYP‐14288 showed better adaptability at high‐temperature stress than the parental isolate (optimal growth temperatures were 30 °C for the high‐resistance mutants and 25 °C for JA8) and SYP‐14288 could induce many biochemical changes between mutants and their parental isolates, whether or not an epigenetic marker such as 6 mA was involved in SYP‐14288‐resistance in P. capsici could be further explored.…”
Section: Discussionsupporting
confidence: 54%
“…It has been reported that N6‐methyldeoxyadenine (6 mA) is a transgenerational epigenetic signal for mitochondrial stress adaptation in Caenorhabditis elegans , and Zhang et al . reported that more transposable elements were demethylated under high‐temperature stress in cotton . Combining our findings that the high‐resistance mutants against SYP‐14288 showed better adaptability at high‐temperature stress than the parental isolate (optimal growth temperatures were 30 °C for the high‐resistance mutants and 25 °C for JA8) and SYP‐14288 could induce many biochemical changes between mutants and their parental isolates, whether or not an epigenetic marker such as 6 mA was involved in SYP‐14288‐resistance in P. capsici could be further explored.…”
Section: Discussionsupporting
confidence: 54%
“…ROS homeostasis is essential for normal anther and pollen development [40,62,85], whereas excessive accumulation of ROS in anthers leads to cell apoptosis and male sterility [9,35,86,87,88]. In this study, a lower extent of H 2 O 2 production but a higher level of ATP synthesis was found in maintainer line ZB compared to ZBA (Figure 6c,d).…”
Section: Discussionmentioning
confidence: 48%
“…DNA methylation has been recognized as a new regulator of plant growth, development, and stress response [34,64,65,66,67,68]. Some researchers have reported that dynamic changes in DNA methylation are involved in the regulation of photoperiod- and/or thermosensitive GMS in rice [69,70,71] and cotton [35,40]; GMS in wheat [38], cabbage [41], and tomato [42]; and CMS in rice [37] and maize [39]. However, the genome-wide cytosine methylation profile and the possible role of DNA methylation in cotton CMS have not been reported so far.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations